Antidepressant action of ketamine via mTOR is mediated by inhibition of nitrergic Rheb degradation - Harraz, Maged M. (Mol Psychiatry, 2016)
As traditional antidepressants act only after weeks/months, the discovery that ketamine, an antagonist of glutamate/NMDA receptors, elicits antidepressant actions in hours has been transformative. Its mechanism of action has been elusive, though enhanced mTOR signaling is a major feature. We report a novel signaling pathway wherein NMDA receptor activation stimulates generation of nitric oxide (NO), which S-nitrosylates glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Nitrosylated GAPDH complexes with the ubiquitin-E3-ligase Siah1 and Rheb, a small G protein that activates mTOR. Siah1 degrades Rheb leading to reduced mTOR signaling, while ketamine, conversely, stabilizes Rheb which enhances mTOR signaling. Drugs selectively targeting components of this pathway may offer novel approaches to the treatment of depression.